Reductions in C‐reactive protein in older adults with type 2 diabetes are related to improvements in body composition following a randomized controlled trial of resistance training. Issue 2 (12th February 2014) - Mavros, Yorgi; Kay, Shelley; Simpson, Kylie A.; Baker, Michael K.; Wang, Yi; Zhao, Ren R.; Meiklejohn, Jacinda; Climstein, Mike; O'Sullivan, Anthony J.; de Vos, Nathan; Baune, Bernhard T.; Blair, Steven N.; et al.
Abstract : Background: Reductions in skeletal muscle mass and increased adiposity are key elements in the aging process and in the pathophysiology of several chronic diseases. Systemic low grade inflammation associated with obesity has been shown to accelerate the age‐related decline in skeletal muscle. The aim of this investigation was to determine the effects of 12 months of progressive resistance training (PRT) on systemic inflammation, and whether reductions in systemic inflammation were associated with changes in body composition. We hypothesized that reductions in systemic inflammation following 12 months of PRT in older adults with type 2 diabetes would be associated with reductions in adiposity and increases in skeletal muscle mass. Methods: Participants ( n  = 103) were randomized to receive either PRT or sham‐exercise, 3 days a week for 12 months. C‐reactive protein (CRP) was used to assess systemic inflammation. Skeletal muscle mass and total fat mass were determined using bioelectrical impedance. Results: Twelve months of PRT tended to reduce CRP compared to sham exercise (β = −0.25, p  = 0.087). Using linear mixed‐effects models, the hypothesized relationships between body composition adaptations and CRP changes were significantly stronger for skeletal muscle mass ( p  = 0.04) and tended to be stronger for total fat mass ( p  = 0.07) following PRT when compared to sham‐exercise. Using univariate regression models, stratified by group allocation, reductions in CRP were associated with increases in skeletal muscle mass ( p  = 0.01) and reductions in total fat mass ( p  = 0.02) in the PRT group, but not in the sham‐exercise group ( p  = 0.87 and p  = 0.32, respectively). Conclusions: We have shown for the first time that reductions in systemic inflammation in older adults with type 2 diabetes following PRT were associated with increases in skeletal muscle mass. Furthermore, reductions in CRP were associated with reductions in adiposity, but only when associated with PRT. Lifestyle interventions aimed at reducing systemic inflammation in older adults with type 2 diabetes should therefore incorporate anabolic exercise such as PRT to optimize the anti‐inflammatory benefits of favorable body composition adaptations.